Addressing Earlobe Elongation: A Systematic Review of Surgical Reduction Techniques in the Aging Population - Aref Nassar, MD, MBE; Carla Nassar, Msc, DDS; Elia Kassouf, MD; Marc Aoude, MD; Charbel El Feghaly, MD; Marwan Nasr, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Aging affects all the components of the face, and the earlobe stands among them. Elongation of the earlobes necessitates surgical correction to restore the youthful ear shape. Methods:. A comprehensive literature search was conducted across the PubMed, Google Scholar, and Cochrane databases. The quality of the included studies was systematically assessed, and data pertaining to surgical earlobe reduction was extracted. Results:. Thirteen articles that closely matched the study objectives were included in this systematic review. We regrouped these techniques into 3 categories: those involving inferior margin excision of the earlobe, those involving anterior earlobe resection, and the third group comprising other methods. To aid in clinical decision-making, we created an algorithm to guide the choice of the procedure. Conclusions:. Proper management of earlobe ptosis and pseudoptosis enhances facial harmony. By outlining the available techniques and providing a treatment algorithm, we emphasize the importance of incorporating earlobe reduction into comprehensive facial rejuvenation strategies.